2023
DOI: 10.3390/microorganisms11020441
|View full text |Cite
|
Sign up to set email alerts
|

Bio-Converted Spirulina for Nutraceutical Chewing Candy Formulations Rich in L-Glutamic and Gamma-Aminobutyric Acids

Abstract: This study aimed at evaluating changes of microalgae Spirulina during its fermentation with Lactiplantibacillus plantarum No. 122 strain, and further at incorporating Spirulina bio-converted for nutraceuticals rich in L-glutamic (L-Glu) and gamma-aminobutyric acids (GABA) into sucrose-free chewing candy (gummy) preparations. Fermented Spirulina had higher b* (yellowness) coordinates than untreated (non-fermented), and fermentation duration (24 and 48 h) had a statistically significant effect on colour coordina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…Through fermentation, the levels of L‐glutamic acid (L‐Glu) and gamma‐aminobutyric acid (GABA) in A. platensis increased significantly, which can reduce neuronal activity and prevent overheating of nerve cells. To mask the undesirable odour of A. platensis , the chewable with 0.2 μL of citrus essential oil was rated the highest, and 0.1 μL of Rehmannia essential oil was most effective in stimulating positive emotions in the evaluators (Bartkiene et al ., 2023). Moreover, Münzel & Daiber (2019) identified a decapeptide in A. platensis that enhances endothelial nitric oxide synthase (eNOS) activity, thereby acting as a vasoprotective and hypotensive agent.…”
Section: Application As Functional Foods Of Arthrospira Platensismentioning
confidence: 99%
“…Through fermentation, the levels of L‐glutamic acid (L‐Glu) and gamma‐aminobutyric acid (GABA) in A. platensis increased significantly, which can reduce neuronal activity and prevent overheating of nerve cells. To mask the undesirable odour of A. platensis , the chewable with 0.2 μL of citrus essential oil was rated the highest, and 0.1 μL of Rehmannia essential oil was most effective in stimulating positive emotions in the evaluators (Bartkiene et al ., 2023). Moreover, Münzel & Daiber (2019) identified a decapeptide in A. platensis that enhances endothelial nitric oxide synthase (eNOS) activity, thereby acting as a vasoprotective and hypotensive agent.…”
Section: Application As Functional Foods Of Arthrospira Platensismentioning
confidence: 99%
“…Several studies have reported the production of fruit candies using various fresh fruits, including unripe mango ( 12 ). Acetic acid, alcoholic and lactic acid-fermented apple juice products ( 13 ), as well as fermented algae such as Spirulina ( 14 ) have been used to produce chewy candies. The production of soft candies (gummy jellies) by adding pomegranate juice ( 15 ) and other natural extracts is well documented.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the biological activity of LAB and their enzymatic systems, a number of biochemical processes occur during fermentation, modifying the raw materials and leading to the production of foods with pleasant tastes, specific aromas and textures [ 14 , 15 , 16 , 17 , 18 , 19 ]. The use of lactic acid starter cultures enables the production of a wide range of products of animal and plant origin.…”
Section: Introductionmentioning
confidence: 99%